1994
DOI: 10.2307/2967190
|View full text |Cite
|
Sign up to set email alerts
|

The Continuing Significance of Desegregation: School Racial Composition and African American Inclusion in American Society

Abstract: JSTOR is a not-for-profit service that helps scholars, researchers, and students discover, use, and build upon a wide range of content in a trusted digital archive. We use information technology and tools to increase productivity and facilitate new forms of scholarship. For more information about JSTOR, please contact support@jstor.org.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
29
0

Year Published

1998
1998
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(30 citation statements)
references
References 10 publications
1
29
0
Order By: Relevance
“…Research concerning racial diversity has accordingly identified, specific to these children, numerous benefits of greater integration. For instance, students of color attending more integrated schools tend to have access to improved educational resources and opportunities, as well as to an environment stressing higher achievement (Braddock, 1980;Carter, 1996;Dawkins & Braddock, 1994;Natriello, Welner 354 These new, statistically sophisticated analyses of high-quality databases provide strong evidence that segregated schools harm the achievement of African American students. However, the association between achievement test scores and desegregation depends on many factors, not the least of which is whether students are resegregated within school sites by means of such practices as tracking and ability grouping (Welner, 2001).…”
Section: Methodsmentioning
confidence: 96%
“…Research concerning racial diversity has accordingly identified, specific to these children, numerous benefits of greater integration. For instance, students of color attending more integrated schools tend to have access to improved educational resources and opportunities, as well as to an environment stressing higher achievement (Braddock, 1980;Carter, 1996;Dawkins & Braddock, 1994;Natriello, Welner 354 These new, statistically sophisticated analyses of high-quality databases provide strong evidence that segregated schools harm the achievement of African American students. However, the association between achievement test scores and desegregation depends on many factors, not the least of which is whether students are resegregated within school sites by means of such practices as tracking and ability grouping (Welner, 2001).…”
Section: Methodsmentioning
confidence: 96%
“…These findings have helped researchers understand how individuals perpetuate segregating behaviors, whereas the findings of Dawkins and Braddock (1994) have helped researchers understand the ways in which exposure to integrated settings changes behaviors and helps Blacks obtain greater inclusion in society. Granovetter's (1973) strength of ties theory provides a framework for viewing and describing interpersonal relationships or links between individuals.…”
mentioning
confidence: 94%
“…However, it is important to understand how these gender differences affect social integration as this may influence a student's general social and academic experience as well as his or her experience with students of other races. This experience may affect whether students will choose to segregate or integrate themselves in the future (Braddock 1980;Dawkins and Braddock 1994).…”
Section: Social Integrationmentioning
confidence: 99%
“…Finally, it is important to continue the rich history of sociological inquiry into both the social and the academic effects of desegregation (see Longshore and Prager 1985;Schofield 1991 for reviews) because the experiences students have with those of other races early on in life may very well affect their future educational and occupational choices and experiences (Dawkins and Braddock 1994;Eaton 2001). It is particularly important to understand how integration within the same school may be experienced differently by males and females as this may potentially lead to gender variation in how students approach future integrated situations.…”
mentioning
confidence: 99%